Анализ возможности создания физической модели поражаемости линии электропередач прямыми ударами молнии - Шевченко, Сергей Юрьевич; Данильченко, Дмитрий Алексеевич; Равлик, Александр Михайлович (Национальный технический университет "Харьковский политехнический институт", 2017)
Используя вторую теорему подобия, получены критерии подобия, использование которых позволит наиболее адекватно построить физическую модель линии электропередачи, поражаемой прямыми ударами молнии. Определены факторы, влияющие на поражаемость воздушных линий прямыми ударами молнии. Рассмотрен пример применение второй теоремы подобия для воздушных линий средних классов напряжения. По проведенным расчетам построена модель воздушной линии электропередачи с использованием генератора импульсного напряжение 2,4 МВ для имитации прямого удара молнии.

Using the second theorem of similarity obtained by the similarity criteria, the use of which will most adequately build a physical model of the transmission power line of affected direct lightning strike. Factors influencing the susceptibility of overhead lines to direct lightning strikes were identified. Analysis of the dimensions of the factors influencing the susceptibility of overhead lines direct lightning strike was made. Installed are independent each other parameters. Choose the most optimal system is the LMTI units. An example of the application of the second similarity theorem for overhead lines voltage average classes. Calculated similarity criteria to create a physical model for a pilot study to determine the probability of hitting overhead transmission line direct lightning strike. The adequacy of the experimental models and the possibility of the creation of the physical model in the real world. According to the calculations a model of an overhead transmission line using a generator of pulsed voltage of 2.4 MV to simulate the direct lightning strike.
Analysis of possible creation of physical models affection transmition power lines direct lightning strike
Keywords: вторая теорема подобия; критерии подобия; анализ размерности; воздушная линия электропередачи; similarity criteria; overhead lines